Factors Affecting External Audit Quality in Municipalities of Palestine: Moderating Role of Supreme Audit Institutions - Husni Ibrahim As’ad Rabaiah (Universiti Sains Islam Malaysia, 2024)
Matric: 4181467 (FEM)